Successful weight loss initiation and maintenance among adolescents with overweight and obesity: does age matter?. Issue 3 (9th February 2018) - Rancourt, D.; Jensen, C. D.; Duraccio, K. M.; Evans, E. W.; Wing, R. R.; Jelalian, E.
Summary: Treatments for adolescents with overweight/obesity demonstrate mixed success, which may be due to a lack of consideration for developmental changes during this period. Potential developmental differences in weight loss motivations, weight maintenance behaviours and the role of parents in these efforts were examined in a sample of successful adolescent weight losers. Participants enrolled in the Adolescent Weight Control Registry ( n = 49) self‐reported demographic information and weight history, reasons for weight loss and weight control, weight loss approach and weight maintenance strategies, and perceived parental involvement with weight loss. Associations between age at weight loss initiation and the aforementioned factors were examined using linear and generalized regressions, controlling for highest z‐BMI and sex. Adolescents who were older (≥16 years) at their weight loss initiation were more likely to report losing weight on their own (37.5% vs. 75%, P = 0.01) and reported greater responsibility for their weight loss and weight loss maintenance ( P < 0.001) compared to younger adolescents. Younger age at weight loss initiation was associated with greater parental involvement ( P = 0.005), whereas older age was associated with greater adolescent responsibility for the decision to lose weight ( P = 0.002), the weight loss approach ( P = 0.007) and food choices ( P < 0.001). Findings suggest the importance of considering developmental differences in responsibility for weight loss and maintenance among adolescents with overweight/obesity.